1979
DOI: 10.1111/j.1432-1033.1979.tb12956.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Lysosomal Pathway of Protein Degradation in Isolated Rat Hepatocytes by Ammonia, Methylamine, Chloroquine and Leupeptin

Abstract: 1. Protein degradation in isolated rat hepatocytes was measured as the release of [14C]valine from pre-labelled protein. To reduce background radioactivity, the intracellular ['4C]valine pool was depleted by serial extraction at 37 "C, effecting equilibration between the intracellular pool and the valine-free extracellular medium. After extraction, a small, non-equilibrating intracellular [14C]valine pool remained; this pool could only be labelled in the presence of ongoing protein synthesis, and might represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
252
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 455 publications
(271 citation statements)
references
References 62 publications
16
252
0
Order By: Relevance
“…Calpain inhibitor I-ALLN has also been reported to inhibit the lysosomal proteases cathepsin B, cathepsin L, and the ubiquitin-dependent proteasome complex (27,30,31). Treatment of ts v-Src-expressing CEF undergoing transformation with ammonium chloride, a reputed inhibitor of lysosomal cathepsins (32,33), or the specific proteasome inhibitor, lactacystin (34), had no effect on the characteristics of v-Src transformation (results not shown), indicating that the effects of ALLN were most likely due to calpain inhibition. In addition, treatment of ts v-Src-expressing CEF with ALLM (100 M), which is inhibitory against calpains, but not the …”
Section: Resultsmentioning
confidence: 99%
“…Calpain inhibitor I-ALLN has also been reported to inhibit the lysosomal proteases cathepsin B, cathepsin L, and the ubiquitin-dependent proteasome complex (27,30,31). Treatment of ts v-Src-expressing CEF undergoing transformation with ammonium chloride, a reputed inhibitor of lysosomal cathepsins (32,33), or the specific proteasome inhibitor, lactacystin (34), had no effect on the characteristics of v-Src transformation (results not shown), indicating that the effects of ALLN were most likely due to calpain inhibition. In addition, treatment of ts v-Src-expressing CEF with ALLM (100 M), which is inhibitory against calpains, but not the …”
Section: Resultsmentioning
confidence: 99%
“…Degradation rates (%) were calculated as percentage of the total protein radioactivity at the start of the experiment. Sample preparation and analysis was performed as in [9,10].…”
Section: Measurement Of Protein Degradationmentioning
confidence: 99%
“…The present study indicates that in COR-L42 cells, 1251I-GRP is degraded by endo/exopeptidases. Chloroquine is a weak base which acts by increasing intralysosomal pH, thus inhibiting further processing of ligand-receptor complexes (Wibo & Poole, 1974;Seglen et al, 1979;Marshall & Olefsky, 1979;Poole & Ohkuma, 1981;Maxfield, 1982). Binding studies carried out in the presence of chloroquine showed that after 1251-GRP binding and internalization, cell-associated radioactivity did not decline, indicating that the subsequent degradation of I251-GRP was inhibited by this agent.…”
Section: Discussionmentioning
confidence: 99%